Recruitment and selection process of Rahimafrooz Energy Service Ltd. (RESL) - Rabeya, Taposhe (BRAC University, 2015)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2015.